Evaluación de dos diluyentes Botucrio® e inra96 mediante Crioconservación de células espermáticas en caballos Lucitano y Arabe en el cantón Latacunga - Tigse Vargas, Ángel Fernando (2023)
Equine reproduction is an important and fundamental process in the life of stallions since it allows us to directly improve and renew the different breeds with the desired characteristics according to the breeders, the conservation of sperm cells is a technique of the reproductive processes, one of them is biotechnology at present. The genetic improvement in equines has allowed the use of the best reproductive horses within the study carried out, a selection, preparation, collection, and evaluation of the equine sperm ejaculate was made. Five Arabian horses and five Lusitano horses were chosen to carry out an analysis on the cryopreservation of semen in the two breeds, these stallions are from the Latacunga canton, where the two commercial diluents Botucrio and Inra96 were compared. The characteristics of each one are undoubtedly evident in the macroscopic analysis such as volume, concentration, total motility, progressive motility, color, odor, and pH, In the microscopic characteristics, total motility, progressive motility, percentage of live-dead were evaluated. In the different seminal extractions of equines, it was concluded that the Botucrio diluent in this research gave better macroscopic and microscopic results with 70%, while the Inra96 diluent gave a feasibility result of 30%. Therefore, it is recommended to work with the Botucrio diluent because of its greater efficacy in showing excellent results in the evaluations and its moderate economic cost.